(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
This article presents the experience of implementing a model for higher professional training based on the theoretical proposal of pedagogical mediation of Gutiérrez and Prieto, in the Workshop "Fundamentals of the production of written didactic materials in a distance education system”. The purpose of the experience is to promote adult learning with a participatory methodology, in a dynamic and practical environment. The model is validated in 2018 with a group of 30 academics from the University of El Salvador (UES) with positive results: the usefulness of the initial sections included in the workshop to motivate participation, as well as the usefulness for learning, is verified. of the themes and activities of the workshop in the achievement of the objectives.